Hybrid-integrated version of SBD amplitude detector intended for the 400–600 GHz frequency range - Zorenko, A.V.; Bychok, A.V.; Shynkarenko, V.V.; Kudryk, Ya.Ya.; Slipokurov, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
A finline version of detector with flat Schottky barrier diodes is developed. It is intended for operation in the 400600 GHz frequency range. The detector electrical parameters are studied. The detector conversion ratio at a frequency of 420 GHz is 97 V/W.